Transfer of grain colors to elite wheat cultivars and their characterization. (September 2016) - Garg, Monika; Chawla, Meenakshi; Chunduri, Venkatesh; Kumar, Rohit; Sharma, Saloni; Sharma, Nand Kishor; Kaur, Navneet; Kumar, Aman; Mundey, Jaspreet Kaur; Saini, Manpreet Kaur; Singh, Sukhvinder Pal
Abstract: Plant anthocyanins can act as antioxidants and help in prevention of cardiovascular diseases, diabetes, inflammation, cancer, obesity and aging. In the current study, anthocyanin rich blue, purple and black wheat lines with alien chromosome or its arm and adapted to local growing conditions were developed from low yielding exotic donor lines. Selected pigmented lines with commercial potential, had yield and thousand grain weight equivalent to the high yielding cultivars. Higher anthocyanin content was observed in black followed by blue, purple and amber wheat lines. 22 different anthocyanins could be identified from blue, 23 from purple and 26 from black wheat lines. Purple wheat lines exhibited higher peak intensities of acylated anthocyanidins. Chroma and hue values assisted in the efficient and reliable selection of compound grain colors. Cryo-microtome seed sections indicated presence of purple color in the pericarp all around the seed. The blue color was present in the aleurone layer all around the seed except around the embryo. Highlights: Color wheat lines with yield advantage were developed and analyzed. Several new anthocyanins were detected in colored wheat lines. Chroma and hue values assisted in efficient selection of compound grain color.